KEDUDUKAN BUKTI ILMIAH DALAM PENYELESAIAN PERKARA PERDATA LINGKUNGAN HIDUP - Utomo, Prasetyo; Adlhiyati, Zakki (Verstek, 2026)
Decision Number 29/Pdt.G/2023/PN.Skh is a verdict issued by the Sukoharjo District Court, handling a civil environmental case filed by residents affected by water and air pollution caused by waste discharged by PT Rayon Utama Makmur (PT RUM). This case was examined using the class action mechanism. In this decision, there is an interesting aspect to study, namely the plaintiffs, who are the residents, and the defendant, PT RUM, both submitted scientific evidence to prove their claims and defenses. This article aims to analyze and examine the position and application of scientific evidence in environmental dispute case number 29/Pdt.G/2023/PN.Skh. This article uses a normative-empirical legal research method with a case study approach using data collection techniques, namely interviews and literature studies, which are analyzed using qualitative analysis techniques. Based on the results of the research and discussion, it can be concluded that in this case, the judge based the position and application of scientific evidence on Supreme Court Regulation Number 1 of 2023 concerning Guidelines for Adjudicating Environmental Cases, in which the position of scientific evidence is the result of research which is then supported by expert testimony in court. In case number 29/Pdt.G/2023/PN.Skh, the Plaintiff submitted 14 pieces of evidence of research on testing the air and water of the Gupit River, which was reinforced by 2 expert testimonies in court. Meanwhile, the Defendant submitted 8 pieces of scientific evidence consisting of testing the quality standards of waste discharged from production activities through the results of wastewater and air testing, supported by one expert testimony in court. Although the Plaintiff submitted conclusive scientific evidence, the Panel of Judges rejected all of the Plaintiff's claims against the Defendant and stated that the act of pollution committed by the Defendant was not proven. Thus, PT RUM was declared to have not committed any unlawful act